2005
DOI: 10.1207/s15374424jccp3402_5
|View full text |Cite
|
Sign up to set email alerts
|

Positive Parenting as a Mediator of the Relations Between Parental Psychological Distress and Mental Health Problems of Parentally Bereaved Children

Abstract: This study investigated a positive parenting composite of multiple measures of warmth and consistent discipline as a mediator of the relations between surviving parents' psychological distress and parentally bereaved children's mental health problems using both cross-sectional and prospective longitudinal models. The study included 214 bereaved children ages 7 to 16 and their surviving parent or current caregiver. A multirater, multimethod measurement model of positive parenting was developed. Although the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
93
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 48 publications
7
93
0
1
Order By: Relevance
“…72 Similarly, people with ID experience psychological and behavioral disturbance in reaction to significant life events. [73][74][75][76] In children, the literature suggests that the best predictors of good outcome are those that shield against secondary loss: a good relationship with a surviving parent who is competent in parenting bereaved children [77][78][79][80] and a stable family environment promoted by strong family organization, cohesion, communication, and role differentiation. 8,81 It seems reasonable to infer that maintaining stability in the home is critical for the well-being of bereaved individuals with ID.…”
Section: Secondary Loss and Coping With Griefmentioning
confidence: 99%
“…72 Similarly, people with ID experience psychological and behavioral disturbance in reaction to significant life events. [73][74][75][76] In children, the literature suggests that the best predictors of good outcome are those that shield against secondary loss: a good relationship with a surviving parent who is competent in parenting bereaved children [77][78][79][80] and a stable family environment promoted by strong family organization, cohesion, communication, and role differentiation. 8,81 It seems reasonable to infer that maintaining stability in the home is critical for the well-being of bereaved individuals with ID.…”
Section: Secondary Loss and Coping With Griefmentioning
confidence: 99%
“…Interrater reliability, assessed using mean Kappa (k) (Cohen, 1960) across an average of two or three raters per code, was k = .77 for positive affective tone, k = .83 for back channeling, and k = .80 for head nods. Kwok et al (2005) conducted a CFA to examine a multireporter, multimethod second-order factor model of caregiver-child relationship quality measured by the above questionnaire and behavioral observation measures of positive caregiver-child relationship and questionnaire measures of discipline using the pretest data employed in the current study. They found that the model fits the data adequately (χ 2 [113, N = 211] = 207.45, df = 113, p < .001; CFI = .93; RMSEA = .062; SRMR = .063).…”
Section: Caregiver-child Relationship Qualitymentioning
confidence: 99%
“…They found that the model fits the data adequately (χ 2 [113, N = 211] = 207.45, df = 113, p < .001; CFI = .93; RMSEA = .062; SRMR = .063). A composite of the standardized scores of the measures employed as indicators for the caregiverchild relationship quality construct by Kwok et al (2005) was used in the present study. 3…”
Section: Caregiver-child Relationship Qualitymentioning
confidence: 99%
“…Responsive parenting is fundamental for adaptive child outcomes in development (Kwok et al, 2005). After the death of his or her partner, the surviving parent may have difficulties in carrying out the role of parent (Saldinger, Porterfield, & Cain, 2004).…”
Section: Problem Statementmentioning
confidence: 99%